Pengaruh Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), Non Performing Loan (NPL), dan Net Interest Margin (NIM) terhadap Kinerja Keuangan pada Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Tri Citra Rosidar; Siti Ruhana Dara (UNIVERSITAS KALBIS, 2022)
This study aimed to determine the effect of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) and Net Interest Margin (NIM) of the Financial Performance on Banking Listed in Indonesia Stock Exchange Period 2017 -2019. In this study the population is the company subsector banking listed on the Indonesia Stock Exchange (IDX). The sample of this research is the companies that are included in the 50 most active IDX members in the total trade value in 2019. This study uses panel data regression analysis method. The results of this study are LDR and NPL affect financial performance, while CAR and NIM have no effect on financial performance. However, CAR, LDR, NPL, and NIM simultaneously affect the financial performance.